Depression, anxiety, and stress among undergraduate medical students: A cross-sectional study in Kancheepuram, India - Recharla Chenchu Karthik; Balaji Arumugam; Ajay Chandrasekar VS; Anusuya, Ganesh Shanmugasundaram; Karthick Malarvannan (Asian Journal of Medical Sciences, 2022)
Background: Medical education is recognized as a stressful education that often negatively impacts academic performance, physical health, and psychological health. Aims and Objectives: Hence, the aims and objectives of this study was to assess the prevalence of depression, anxiety, and stress levels among undergraduate medical students. Materials and Methods: A cross-sectional study was conducted at tertiary medical college in Kancheepuram from November 1, 2019, to December 31, 2019. A total of 360 undergraduate medical students were recruited from the 1st year to the final year. Each year was considered a stratum, and from each stratum through simple random sampling, 90 students were selected. A self-administered, pre-designed, pre-tested anonymous questionnaire-depression anxiety and stress scale 21 was used for data collection. CoGuide software was used for statistical analysis. Results: Out of 360 medical students, 157 were male and 203 were female with a mean age of 19.98±1.17. Sixty-six (18.33%) study participants had a family history of mental illness. The overall prevalence of depression was 48.33%, 60.56% had anxiety, and 27.22% had stress. Females were more affected than their male counterparts. The prevalence was significantly more among those having a family history of mental illness. Conclusion: The prevalence of depression was 48.33%, anxiety was 60.56%, and stress was 27.22%. Regular health education, stress counseling, and peer group sessions can reduce the level of mental distress among medical students.